(untitled) (Proceedings of the Global Public Health Conference, 2025)
This cross-sectional study investigated the prevalence, types, and coping strategies associated with cyberbullying among adolescents in Hanoi, Vietnam. This demographic is particularly vulnerable as Vietnamese adolescents lack access to adequate support resources. Using respondent-driven sampling to provide a safe and confidential platform for discussing a sensitive topic, data was collected through self- administered online surveys based on the cyberbullying measurement scale and coping strategy framework developed by Patchin and Hinduja. A total of 253 students aged 13–18 from public schools participated in the study. Results revealed that 51.4% of participants had experienced at least one of six forms of cyberbullying, and 77.9% had witnessed others being cyberbullied. These behaviors often led to emotional distress among victims, emphasizing the significant psychological impact of cyberbullying on adolescents. Additionally, the study explored coping strategies and found that students frequently lacked effective mechanisms to address cyberbullying incidents. The most common response was seeking advice from friends, reported by 40.7% of participants, while fewer students turned to parents, teachers, or professional support systems for help. This limited reliance on adults or institutional resources highlights a potential gap in support systems available to students in the effectiveness or accessibility of current support systems. These findings underscore the urgent need for comprehensive educational interventions aimed at raising awareness about cyberbullying and equipping students with practical tools to manage and respond to such incidents effectively. Schools and policymakers should prioritize the development of programs that foster digital resilience, enhance peer support networks, and encourage the involvement of trusted adults to create a safer online environment for adolescents. Initiatives like peer mentoring programs can empower adolescents to support one another, fostering a safer and more connected online environment.